TRANSFORMATIVE LEADERSHIP IN THE MIDST OF POLITICAL TURMOIL" A STUDY OF SOCIAL DYNAMICS IN SIDENRENG RAPPANG REGENCY - Musmulyadi, Musmulyadi; Akilah, Fahmiah; Artianasari, Nining; Md Shah, Jalihah (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2025)
This study examines how political turmoil affects local leadership practices in Sidenreng Rappang Regency, especially ahead of the Regional Elections. With a mixed methods approach, this study explores the strategic, communication, and ethical dimensions of transformative leadership practices in response to heated political dynamics. Quantitative findings show a strong correlation (R = 0.870) between political instability and changes in leadership styles, which are characterized by increased use of populist and authoritarian approaches. Qualitative data revealed public skepticism of short-term policies and political imagery through social media. Theoretically, the study enriched the literature by incorporating a variety of leadership theories—transformational, transactional, strategic, and ethical—in local contexts. In practical terms, the results of the study confirm the importance of transparency, consistency, and orientation to long-term well-being as the main foundation of effective leadership. The study also highlights the importance of critical public perception and the need for leaders to transcend electoral interests for sustainable development.